The improved (G'/G)-expansion method to the (2+1)-dimensional breaking soliton equation - Naher, Hasibun; Aini Abdullah, Farah (© 2014 Eudoxus Press, LLC, 2016)
This article was published in the Journal of Computational Analysis and Applications [©2014 Eudoxus Press, LLC ] the article link is : http://eds.b.ebscohost.com/eds/detail/detail?sid=d208a030-a0c5-49e3-80af-0972d6420d48%40sessionmgr104&vid=0&hid=108&bdata=JnNpdGU9ZWRzLWxpdmU%3d#AN=92699985&db=aph